2020
DOI: 10.3389/fmolb.2020.586146
|View full text |Cite
|
Sign up to set email alerts
|

Novel TrxR1 Inhibitors Show Potential for Glioma Treatment by Suppressing the Invasion and Sensitizing Glioma Cells to Chemotherapy

Abstract: Currently, available glioblastoma (GBM) treatment remains ineffective, with relapse after initial response and low survival rate of GBM patients. The reasons behind limited capacities for GBM treatment are high tumor heterogeneity, invasiveness, and occurrence of drug resistance. Therefore, developing novel therapeutic strategies is of utmost importance. Thioredoxin reductase (TrxR) is a novel, promising target due to its overexpression in many cancer types and important role in cancer progression. Previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The observed changes in expression of the enzymes may indicate the expression required in individual cell lines to attempt to maintain an intracellular redox balance. In glioma cells, treatment with novel TrxR1 inhibitors increased mRNA expression of Trx and TrxR1 in response to high ROS levels [ 45 ]. In addition, an increase in the TrxR expression may be one of the reasons why luminal cells did not show as much increased radiosensitivity following IQ9 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes in expression of the enzymes may indicate the expression required in individual cell lines to attempt to maintain an intracellular redox balance. In glioma cells, treatment with novel TrxR1 inhibitors increased mRNA expression of Trx and TrxR1 in response to high ROS levels [ 45 ]. In addition, an increase in the TrxR expression may be one of the reasons why luminal cells did not show as much increased radiosensitivity following IQ9 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was noticed during a cell viability assay performed on human keratinocytes (HaCaT) 90,91 as well as neuroblastoma (SH-SY5Y) 90,91 and glioblastoma (U87 and U87-TxR) cell lines 92 . Despite the effective selective action of DVD-445 against cancer cells, it has been observed that neuroblastoma cells remain viable at approximately 80% [90][91][92] . In addition, some DVD-445 analogues also show inhibitory activity against TrxR activity, but not in cancer cells 90 .…”
Section: Synthetic Inhibitors Of Trxrmentioning
confidence: 93%
“…The compound signed as DVD-445 deserves special attention because of its preferential effect on easily proliferating cancer cells 90 . This effect was noticed during a cell viability assay performed on human keratinocytes (HaCaT) 90 , 91 as well as neuroblastoma (SH-SY5Y) 90 , 91 and glioblastoma (U87 and U87-TxR) cell lines 92 . Despite the effective selective action of DVD-445 against cancer cells, it has been observed that neuroblastoma cells remain viable at approximately 80% 90–92 .…”
Section: Modification Of the Trx-trxr Systemmentioning
confidence: 93%
“…To date, temozolomide is still the only adjuvant medicine. Spatial analysis indicated that the in the tumour is responsible for TMZ resistance [14]. Glioma stem cells play key roles in resistance to chemotherapy and radiotherapy [15].…”
Section: Discussionmentioning
confidence: 99%